Plagiarism in scientific publications - Facina, Gil; Cavalcante, Francisco Pimentel; Paulinelli, Régis Resende; Vieira, René Aloisio da Costa (Mastology, 2020)
Plagiarism in scientific publications is a topic of fundamental importance and rarely addressed in the literature. It is associated with ethical issues that go beyond research itself, a fact that values the discussion on the topic. The concept, the main types of plagiarism, ethical relationships, preventive methodologies aiming to minimize their occurrence, diagnostic methodologies, and potential penalties involved are discussed. Every researcher and team involved in publishing articles should be aware of the importance and relevance of not plagiarizing, since being cautious about it is essential to build a solid curriculum on the part of the researcher, and credibility on the part of scientific journals.